The Evolution of LeanStore - Alhomssi, Ahmad Adnan; Haubenschild, Michael; Leis, Viktor (Lecture Notes in Informatics (LNI), Proceedings - Series of the Gesellschaft fur Informatik (GI), 2023)
LeanStore is a high-performance key-value storage engine optimized for many-core processors and NVMe SSDs. This paper provides the first full system overview of all LeanStore components, several of which have not yet been described. We also discuss crucial implementation details, and the evolution of the entire system towards a design that is both simple and efficient.
CRIS-Team Scopus Importer:2023-03-24
Keywords: B-tree; caching; LeanStore; multi-core; SSD; storage engine